Analysis of History Teachers’ Strategies in Adapting Deep Learning Approach: A Qualitative Study at SMA Muhammadiyah 1 Semarang - Sampurna, Basyaarah; Suryadi, Andy (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study analyzes the strategies employed by history teachers in adapting the deep learning approach at SMA Muhammadiyah 1 Semarang. A qualitative method was applied through observation, in-depth interviews, and document analysis. The findings reveal: (1) The history teacher utilized project-based learning, contextual issue discussions, and reflective questioning to enhance students' deep understanding; (2) Major challenges include the limited contextual relevance of historical content and the diversity of student learning characteristics that affect the effectiveness of deep learning implementation; (3) Curriculum coordinator provided structural support through routine training and adaptive instructional design. This approach positively influences students' active engagement and fosters reflective and critical thinking in history education. The study highlights the importance of collaboration between teachers and curriculum developers in reinforcing deep learning practices in history classrooms. These findings are significant in the context of 21st-century education, which prioritizes meaningful learning, conceptual depth, and student-centered engagement as key drivers of educational quality and relevance.